2021
DOI: 10.1371/journal.ppat.1009582
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ALTO-encoding circular RNAs expressed by Merkel cell polyomavirus and trichodysplasia spinulosa polyomavirus

Abstract: Circular RNAs (circRNAs) are a conserved class of RNAs with diverse functions, including serving as messenger RNAs that are translated into peptides. Here we describe circular RNAs generated by human polyomaviruses (HPyVs), some of which encode variants of the previously described alternative large T antigen open reading frame (ALTO) protein. Circular ALTO RNAs (circALTOs) can be detected in virus positive Merkel cell carcinoma (VP-MCC) cell lines and tumor samples. CircALTOs are stable, predominantly located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…The LT and sT encoding region of MCPyV contains an alternative reading frame which encodes the ALTO protein with unknown function [ 359 ]. A recent study identified two viral circRNAs derived from ALTO mRNA, circALTO1 (762 nucleotides in length) and circALTO2 (940 nucleotides long) in MCPyV-positive MCC cell lines, whereas only circALTO2 was detected in virus-positive tumors, suggesting that the abundance of the circALTO isoforms might differ in vivo [ 346 ]. The circALTOs were stable, predominantly located in the cytoplasm, and enriched in exosomes.…”
Section: Oncoviruses and Circrnasmentioning
confidence: 99%
See 2 more Smart Citations
“…The LT and sT encoding region of MCPyV contains an alternative reading frame which encodes the ALTO protein with unknown function [ 359 ]. A recent study identified two viral circRNAs derived from ALTO mRNA, circALTO1 (762 nucleotides in length) and circALTO2 (940 nucleotides long) in MCPyV-positive MCC cell lines, whereas only circALTO2 was detected in virus-positive tumors, suggesting that the abundance of the circALTO isoforms might differ in vivo [ 346 ]. The circALTOs were stable, predominantly located in the cytoplasm, and enriched in exosomes.…”
Section: Oncoviruses and Circrnasmentioning
confidence: 99%
“…Proteins encoded by these genes included components of NFκB signaling pathway, transcription factors, and inflammatory and anti-viral cytokines, suggesting the circALTO can modulate genes and pathways implicated in MCPyV pathogenesis. As circALTOs are enriched in exosomes, it is tempting to the speculate that circALTOs could prepare recipient cells for MCPyV infection and promote tumor development [ 346 ]. MCPyV may encode additional circRNAs because potential circRNAs were predicted upstream of genes encoding the capsid protein VP2 [ 346 ].…”
Section: Oncoviruses and Circrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors hypothesize that overprinting genes such as these evolve in viruses as a strategy to maximize the coding potential of relatively small genomes (Carter et al, 2013 ). Recently, several ALTO-encoding circular RNAs have been identified in MCPyV-positive MCC cell lines and tumor tissues (Yang et al, 2021 ). MCPyV ALTO translated from these circular RNAs has the ability to transactivate recombinant promoters, as well as, a number of key cellular genes involved in MCPyV pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…MCPyV ALTO translated from these circular RNAs has the ability to transactivate recombinant promoters, as well as, a number of key cellular genes involved in MCPyV pathogenesis. Therefore, MCPyV ALTO protein may be able to modulate MCPyV infectious and tumorigenic potential through transcription regulation (Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%